Co-Production of the Provision of Public Goods by the Community in Darungan Village, Jember Regency - Supranoto Supranoto; Mohammad Baladdudin Dayar; Faiqoh Faiqoh (Indonesian Association for Public Administration (IAPA), 2022)
This paper is the development of research that examines the long experience of Darungan Village, Jember Regency in providing public goods in the form of clean water for its citizens. The study was conducted from the institutional perspective of the Ostrom (1980) and Bromley (1989) model and focused on a) the role of the parties, particularly the government and society, in co-production institutions, and b) the challenges and obstacles faced. The research was conducted using a descriptive qualitative approach, involving some informants from both the community and village government to the district government. All informants were selected on the basis that they knew the process being studied due to their direct involvement. Primary data were collected using in-depth interviews, participatory observation, and focus group discussions. Secondary data was collected by the document study method. All data were tested for validity by triangulation of sources and methods before being analyzed by an interactive analysis model. Research finds that co-production institutions in the provision of clean water experience various obstacles in line with the ups and downs of the government's role.